The Relationship of Organizing National Sports Events to Local Tax Revenue in Indonesia - Budiarto, Susan; Qibthiyyah, Riatu Mariatul (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2022)
The Indonesia National Sports Event, commonly known as Pekan Olahraga Nasional (PON), is a quadrennial multi-sport event involving athletes from all provinces in Indonesia. The PON is expected to encourage economic growth to increase local tax revenue for the host. This study aimed to measure the impact of PON event to local tax revenue, specifically taxes from hotels, restaurant, entertainment and advertisement. Using Even study approach, this study measured the effect of PON event from PON 2000 to PON 2016, involving local tax revenue data from 105 districts and cities in the provinces of PON events. The empirical test results show that PON affects total local tax revenue, restaurant tax, and entertainment tax in the short term, but has no impact on hotel and advertisement tax revenue. This study suggested the local governments to manage and maintain the facilities and infrastructure so that the local government can utilize these facilities andinfrastructure after the PON ends to add local tax revenue. Improving the performance in handling PON can also improve the local image to attract the public’s interest and investors to the area.